Segmentasi Wisatawan Domestik Terhadap Keputusan Memilih Destinasi Tawangmanggu - Elizabet Sagala, Afrilia (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
Tawangmangu as a tourist destination still has an attraction for local tourists. The diversity of tourist objects, uniqueness, good image and quality of service are important factors that encourage tourists to come to Tawangmangu. The result of the X1 (demographic segment) value is 0.889, X2 (psychographic segment) is 1.614, X3 (behavioral segment) is 6.789, while the tt value in this study is 1.897. It can be said that the behavioral segment in the form of benefits that are used by sensations can be a place to relieve fatigue (healing) on holidays at affordable prices, the level of visitor loyalty is very significant because of the sample profile visiting> 3 visits to the Tawangmanggu Destination, then the independent variable (demographic segment) , psychographic segment, behavioral segment) together contributed to the dependent variable (the decision to visit Tawangmanggu) by 43.9% and the remaining 56.1% was influenced by other variables not included in this study. The other variables are probably the variables contained in the marketing mix related to promotion, price, and other variables in the elements of tourism activities, namely: something to see, something to do, something to buy. Tourists who come are dominated by productive tourists, junior high / high school education, diverse jobs, middle to upper income, and visiting destinations for recreation, enjoying various regional crowds, culinary and enjoying the unique scenery of Tawangmangu with family. Tourists generally have high loyalty as visitors. Geographical factors in the form of cold temperatures, accessibility and facilities significantly influence the decision to visit